Inclusive assessment for linguistically diverse learners in higher education - Kaur, Amrita; Noman, Mohammad; Nordin, Hasniza (Taylor & Francis Group, 2016)
As classrooms become increasingly diverse in higher education, educators are emphasising inclusive practices in teaching and learning to accommodate the needs of diverse learners.There is also an emerging need for an inclusive approach in assessment for accessibility, opportunity, relevance and engagement.This study, using design-based research guidelines with student–faculty partnership, designed, developed, implemented and evaluated contextually sensitive assessment protocol as inclusive and fair assessment.Data from students’ reflections and face-to-face interviews with open-ended questions suggested that, despite concerns such as potential bias, time and accommodation challenges, such assessment practices can make valuable contributions in creating a positive learning environment, improving relatedness and self-esteem and motivating and engaging students for better effort and effective learning.Implications for higher education practitioners with diverse learners are discussed.